Do You Need to Travel? Mapping Face-to-Face Communication Objectives to Technology Affordances. (December 2020) - Dianiska, Rachel E.; Peasley, Charles J.; Wilson, Nicholas; Barnett, Neil; Hammel, Leilani; Purdy, Ben; Wu, Peggy; Shirtcliff, Elizabeth; Oliver, James H.; Gilbert, Stephen B.
Computer-mediated communications (CMC) can be used as a substitute for face-to-face (FtF) meetings but their effectiveness is highly context dependent. This paper describes a theoretical framework and initial experimental design for characterizing a travel replacement threshold. This effort begins with a use case of remote engineering maintenance training, conducted in three conditions: side-by-side (physically proximate), teleconference (using off-the-shelf software), and a custom VR/AR system designed to provide the apprentice with a virtual view of both the instructor's larger scale lab and smaller scale workbench. The research hypotheses, experimental protocol, and dependent measures are described. The task involves an instructor demonstrating a circuit board troubleshooting task to a remote apprentice. The apprentice then completes the trained task independently, and performance and subject preferences are compared across conditions. The details of this paper, the result of extensive literature review and winnowing of variables, may assist researchers exploring CMC, training, or social communication.